2014
DOI: 10.1128/iai.00035-14
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Airway Inflammation Decreases Lung Bacterial Burden following Acute Klebsiella pneumoniae Infection in a Neutrophil- and CCL8-Dependent Manner

Abstract: f The Th17 cytokines interleukin-17A (IL-17A), IL-17F, and IL-22 are critical for the lung immune response to a variety of bacterial pathogens, including Klebsiella pneumoniae. Th2 cytokine expression in the airways is a characteristic feature of asthma and allergic airway inflammation. The Th2 cytokines IL-4 and IL-13 diminish ex vivo and in vivo IL-17A protein expression by Th17 cells. To determine the effect of IL-4 and IL-13 on IL-17-dependent lung immune responses to acute bacterial infection, we develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 98 publications
(131 reference statements)
0
12
1
Order By: Relevance
“…We concluded from these results that eosinophils and neutrophils were not required for enhanced resistance to pneumococcal pneumonia following ALI. In contrast to our findings, increased resistance of mice to Klebsiella pneumoniae following ALI did require neutrophils (32), a finding that is consistent with a requirement of neutrophils for protection against pulmonary K. pneumoniae infections (35). For pneumococcal infection, on the other hand, neutrophil recruitment is thought to play a major role in control of bacterial colonization while having a limited impact during acute lung infections (36)(37)(38).…”
Section: Discussioncontrasting
confidence: 56%
“…We concluded from these results that eosinophils and neutrophils were not required for enhanced resistance to pneumococcal pneumonia following ALI. In contrast to our findings, increased resistance of mice to Klebsiella pneumoniae following ALI did require neutrophils (32), a finding that is consistent with a requirement of neutrophils for protection against pulmonary K. pneumoniae infections (35). For pneumococcal infection, on the other hand, neutrophil recruitment is thought to play a major role in control of bacterial colonization while having a limited impact during acute lung infections (36)(37)(38).…”
Section: Discussioncontrasting
confidence: 56%
“…Mice were anesthetized with ketamine and xylazine and 2 × 10 3 colony forming units were administered intra-nasally32. Samples were collected after 6, 24, 48, or 72 hours.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that strong neutrophilia induced by asthma sensitization in STAT-6 −/− mice (Figure S2 in Supplementary Material) could be sufficient to increase resistance to S. pneumoniae in our model. Interestingly, a recent study ( 79 ) in a mouse model reported that allergic asthma also decreases lung infection with Klebsiella pneumoniae in a neutrophil-dependent and IL-4- and IL-17-independent manner.…”
Section: Discussionmentioning
confidence: 99%